THE EFFECT OF NEED FOR ACHIEVEMENT AND SELF-EFFICACY ON ENTREPRENEURIAL INTENTION - Putri, Shafila Tasya Kamila; Eryanto, Henry; Faslah, Roni (Faculty of Economics and Business, Universitas Negeri Jakarta, 2022)
The purpose of this study was to determine the effect of the need for achievement and self-efficacy on entrepreneurial intention amongst students of the Faculty of Economics in Jakarta State University class 2017 and 2018. This study employs a quantitative method using the questionnaire instrument. Data is obtained from 216 respondents comprising the class of 2017 and 2018 students. The model in this study uses a path analysis model. The analytical technique used in this study uses the SEM (Structural Equation Modeling) model which is operated with the SmartPLS version 3.0 program for hypothesis testing. This study found that the need for achievement and self-efficacy positively and significantly affected entrepreneurial intention. These results showed that students will have high entrepreneurial intentions if they have a strong drive in individual characteristics to try hard and perform various tasks as well as possible in order to fulfill needs by setting goals and having individual confidence in their abilities to do various jobs effectively. Persistent in order to achieve the goals that have been planned and can complete them.